Gate of the Palace of Adil Shah, Old Goa: A misunderstood monument - Santos, Joaquim Rodrigues dos (2022)
In the mid-nineteenth century, all that was left of the city of Goa, the former Portuguese capital of the Estado da Índia, was a vast field of palm trees dotted by some large churches stoically resisting time and surrounded by the many ruins of what was once known as “Golden Goa”. Among all the ruins of Old Goa stands a built structure, now classified as a national monument of India, known as the Gate of the Palace of Adil Shah. However, this structure is not a ruin but can rather be considered a folly ruin erected at the beginning of the twentieth century. This article aims to study this structure by analysing its evolution, the creation of its late-Romantic ruinism and its appropriation for ideological purposes, focusing also on the ongoing misunderstanding of it.